A novel mutation in SLC25A46 causes optic atrophy and progressive limb spasticity, with no cerebellar atrophy or axonal neuropathy. Issue 2 (30th March 2017) - Sulaiman, R.A.; Patel, N.; Alsharif, H.; Arold, S.T.; Alkuraya, F.S.
Abstract :